Influence Of Cuisenaire Rods On Students’ Perception In Teaching Fractions At Dambia College Of Education - Togah, Frederick Kwasi (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
It’s too bad that Teacher Trainees, who would be in charge of carrying out government education policies in elementary schools, don’t do well when it comes to the Teaching Procedures, Strategies, and Methodologies needed to teach elementary math.This study was made for second-year education students at Dambai College of Education to help them get better at teaching how to add and subtract fractions with different denominators using real-world objects. Using Cuisenaire Rods as an intervention tool, the researcher came up with ways to improve how this important math concept is taught to students.The study involved fifty (50) Second-Year students, including 41 males and nine females, out of a total of two hundred (200). Samples for the study were selected using both stratified and random sampling strategies. The primary instrument for data collection was tests. The raw scores from both the pre-test and the post-test were put into Statistical Package for the Social Sciences (SPSS) for analysis and interpretation.At the conclusion of the analysis and discussion of results, it was determined that the intervention tool led to a considerable improvement in student performance. The study recommends that tutors teaching mathematics in the Colleges of Education must be familiar with its usage so that they can incorporate these materials in their teaching process and more emphasis should be laid on the use of Cuisenaire rods especially at the Colleges of Education.